"Becoming a Better Man": Narrating Masculinities After Childhood Emotional Abuse. Issue 1 (February 2018) - Moulding, Nicole
Childhood emotional abuse (CEA) is the most common and psychologically harmful form of child abuse. While there has been attention to how gender discourses and power relations frame other forms of interpersonal violence and abuse, there has been no research into the gendered dimensions of CEA. This article reports on the findings from a qualitative interview study with men who have these backgrounds. The study was framed by a poststructural feminist understanding of gender, discourse, and power and R. W. Connell's concept of hegemonic masculinity and social practices of gender. Narrative-discursive analysis revealed a powerful discourse about "becoming a better man" in spite of abuse through practices of hegemonic masculinity, particularly the control of emotion and prevailing over abusers. The article considers the positive and negative implications for abused men's subjectivities as well as those for women and wider gender power relations. The article also considers gender-aware approaches for social workers and other professionals working with individuals who have these backgrounds.